2019
DOI: 10.1111/jopr.13103
|View full text |Cite
|
Sign up to set email alerts
|

Fracture Resistance of Additively Manufactured Zirconia Crowns when Cemented to Implant Supported Zirconia Abutments: An in vitro Study

Abstract: Purpose To compare the fracture resistance of implant‐supported milled zirconia, milled lithium disilicate, and additively manufactured zirconia crowns. Materials and Methods Maxillary cast with a dental implant replacing right second bicuspid was obtained. Custom abutments and full‐contour crowns for milled zirconia, milled lithium disilicate, and additively manufactured zirconia crowns (n = 10/group) were digitally designed and fabricated. The crowns were cemented to implant‐supported zirconia abutments and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
56
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(65 citation statements)
references
References 24 publications
0
56
0
2
Order By: Relevance
“…The fracture resistance of implant-supported milled zirconia, milled lithium disilicate, and stereolithography (SLA) additively manufactured zirconia crowns were compared by Zandinejad et al [ 18 ]. Zirconia implant abutments were designed with a chamfer finish line and having 6 mm buccal and lingual wall height and 4 mm proximal wall height.…”
Section: Dental Applications Of Am Zirconia Ceramicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The fracture resistance of implant-supported milled zirconia, milled lithium disilicate, and stereolithography (SLA) additively manufactured zirconia crowns were compared by Zandinejad et al [ 18 ]. Zirconia implant abutments were designed with a chamfer finish line and having 6 mm buccal and lingual wall height and 4 mm proximal wall height.…”
Section: Dental Applications Of Am Zirconia Ceramicsmentioning
confidence: 99%
“…The American Society for Testing and Materials (ASTM) divides AM technologies into seven classifications to construct a product layer by layer: stereolithography (SLA), material jetting (MJ), material extrusion (ME), binder jetting (BJ), powder base fusion (PBF), sheet lamination (SL), and direct energy deposition (DEP), as all can be used to form ceramic components [ 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The advantages of provisional restorations via CAD-CAM process over conventional curing include increased durability [1,3,4,12,13], improved fit [3,4] and color stability [4]. However, fabrication with milling also has disadvantages: material waste, introduction of microcracks and limited reproduction of surface details depending on the size of the milling instrumentation [14].…”
Section: Introductionmentioning
confidence: 99%
“…With the increasing availability of 3D printers, digitally-designed provisional restorations can be printed in addition to being milled. Additive manufacturing creates less raw material waste, reduces manufacturing time and allows for mass production as compared to milling [6,14,15] but 3D-printed structures have limited shade selection, display a less finished surface due to anisotropy and the staircase effect and require expensive post-processing for ceramic [6,14]. Recently, investigators found that the accuracy of dental restorations fabricated by additive manufacturing methods is higher than that of subtractive methods [16].…”
Section: Introductionmentioning
confidence: 99%
“…The thickness of the crown ranged from 1.0 mm (at the margin) to 2.0 mm (at the occlusal surface). The STL 2 file was used to fabricate (CeraMaker 900; 3DCeram Co. Lemonge, France) 10 full-contour zirconia (3DMix ZrO 2 paste; 3DCeram Co. Lemonge, France) crowns [38]. Thereafter, the STL 2 file was split in thickness into 2 layers (Figure 3).…”
Section: Methodsmentioning
confidence: 99%